A novel link between silent information regulator 1 and autophagy in cerebral ischemia-reperfusion - Tang, Yingying; Xie, Jiaqian; Chen, Xiaoping; Sun, Lihong; Xu, Lili; Chen, Xinzhong (Frontiers in Neuroscience, 2022)
Cerebral ischemia is one of the leading causes of death and disability worldwide. Although revascularization via reperfusion combined with advanced anticoagulant therapy is currently a gold standard treatment for patients, the reperfusion itself also results in a serious dysfunction termed cerebral ischemia-reperfusion (I/R) injury. Silent information regulation protein 1 (Sirtuin 1, SIRT1) is a classic NAD+-dependent deacetylase that has been proposed as an important mediator in the alleviation of cerebral ischemia through modulating multiple physiological processes, including apoptosis, inflammation, DNA repair, oxidative stress, and autophagy. Recent evidence suggests that SIRT1-mediated autophagy plays a key role in the pathophysiological process of cerebral I/R injury. SIRT1 could both activate and inhibit the autophagy process by mediating different autophagy pathways, such as the SIRT1-FOXOs pathway, SIRT1-AMPK pathway, and SIRT1-p53 pathway. However, the autophagic roles of SIRT1 in cerebral I/R injury have not been systematically summarized. Here, in this review, we will first introduce the molecular mechanisms and effects of SIRT1 in cerebral ischemia and I/R injury. Next, we will discuss the involvement of autophagy in the pathogenesis of cerebral I/R injury. Finally, we will summarize the latest advances in the interaction between SIRT1 and autophagy-related signaling pathways in cerebral I/R injury. A good understanding of these relationships would serve to consolidate a framework of mechanisms underlying SIRT1’s neuroprotective effects and provide evidence for the development of drugs targeting SIRT1.